Assessment of pectinase-producing fungi isolated from soil and the use of orange waste as a substrate for pectinase production - Davanso, Maísa [UNESP]; Atsakou, Abra Eli [UNESP]; Gattás, Edwil A. L. [UNESP]; Paula, Ariela Veloso de [UNESP] (My University, 2019)
Pectinases are important enzymes for their potential applications in different industries such animal feed, agricultural, textile, beverage, food processing, oil extraction, etc. Ten fungal species were isolated from the soil and screened for production of pectinase enzyme by using the pectin agar medium. Pectinolytic enzymes synthesis were attained at a temperature of 30 °C and activities were determined after a seven-days culture of Aspergillus sp. 391 and Aspergillus sp. 031, in a basic medium containing 2% citrus pectin and as the sole carbon source. The extract enzymatic showed an optimum activity for exo-polygalacturonase (PG) and pectin lyase (PNL) against galacturonic acid and pectin at pH 4.5 and 5.5, respectively. There were variations in PG and PNL enzymes levels produced in culture filtrates obtained of Aspergillus sp. 391 with addition of citrus waste (2.0 and 4.0% w/v) to the medium. Maximum activity for PNL activity was observed in the medium containing 5% pectin or 4% citrus waste, as sole carbon source, after 7 days of growth. The results showed that the isolate Aspergillus sp. 391 is a promising for pectinolytic enzymes production at the industrial level.
Avaliação de fungos produtores de pectinase isolados do solo e uso de resíduos de laranja como substrato para a produção de pectinase
Keywords: Activity; Aspergillus sp; Enzyme Production; Pectinase